Perceptions of pre-service teachers towards online learning at a teacher education college in Zimbabwe - Matorevhu, Alois; Madzamba, Havatidi (Journal of Research in Instructional, 2025)
At the end of 2019, the advent of the COVID-19 pandemic prompted an immediate knee-jerk response in many countries worldwide to shut down all learning institutions, from preschool to university level. This unforeseen abrupt closure of most educational institutions compelled the conversion of face-to-face learning to a fully online or blended/hybrid format in a very short transitional time. While the advantages of online learning are apparent, its effective use in many universities and colleges is very complex and challenging. This may be due to factors like large student numbers, lack of appropriate gadgets, poor internet connectivity, and expensive data bundles. In the context of both challenges and benefits of online learning, this study sought to explore perceptions of pre-service teachers (students) at a teacher education college in Zimbabwe on their experience in the use of a particular online teaching and learning platform. We used a semi-structured questionnaire and interviews in this case study to gather data. Findings show that pre-service teachers perceived the online learning platform to be useful in facilitating learning by enabling them to learn anytime from any place. However, the pre-service teachers indicated that, if given the opportunity to choose, they would prefer face-to-face learning due to their inability to purchase laptops, the high cost of data required to stay connected to the internet, and their lack of proficiency in using the online learning platform. Based on findings, recommendations are given for enhancing the use of online platforms for teaching and learning.